Self-starting harmonic mode-locked Tm-Bi co-doped germanate fiber laser with carbon nanotube-based saturable absorber - Saidin, N.; Zen, D.I.M.; Damanhuri, S.S.A.; Harun, Sulaiman Wadi; Ahmad, Harith; Ahmad, F.; Dimyati, K.; Halder, A.; Paul, Mukul Chandra; Pal, M.; Bhadra, S.K. (Optical Society of America, 2013)
We report a ring cavity passively harmonic mode-locked fiber laser using a newly developed thuliumbismuth co-doped fiber (TBF) as a gain medium in conjunction with a carbon nanotube (CNT)-based saturable absorber. The TBF laser generates a third harmonic mode-locked soliton pulse train with a high repetition rate of 50 MHz and a pulse duration of 1.86 ps. The laser operates at 1 901.6 nm with an average power of 6.6 mW, corresponding to a pulse energy of 0.132 nJ, at a 1 552 nm pump power of 723.3 mW.